Fire guts old hotel - Ladd, Joan (Raton Range Raton, NM, 1979)
Article is about the fire that destroyed the Cimarron Hotel.
Newspaper article + photograph of Cimarron Hotel
Mater List Item # 58
File location is in the New Mexico File Cabinets
Keywords: Potter, James -- Cimarron Fire Chief; Holmes, Norman; Cimarron Hotel; Cimarron Fire Department; Philmont Fire Department; Hotel Fires; Business Fires; Water Damage; Hotel Damage; Cimarron, New Mexico